Tooth & claw : the dinosaur wars - Noyes, Deborah (Viking, 2019)
Follows the epic rivalry between scientists Edward Drinker Cope and Othniel Charles Marsh who raced to uncover dinosaur fossils in the American West during the nineteenth century. Describes how the two discovered dozens of major dinosaur species and founded the discipline of paleontology in America, but their thirty-year war wrecked both men's professional and private lives. Features sidebars, illustrations, and further reading.